Theological Educators, Technology and the Path Ahead - Delamarter, Steve (Teaching theology and religion, 2005)
Digital technology offers a host of opportunities and challenges for theological education. In this essay the author considers possible futures for theological education through creative uses of technology. The first half of the essay identifies five areas in which theological educators have had to gain technology skills in the last several years: 1. Individual facility with a personal computer; 2. Functioning capably in a connected world; 3. Information literacy for research and ministry; 4. Technology for face-to-face instruction; and 5. Technology for asynchronous teaching and learning. The second half of the essay identifies the forces that will likely drive technology learning for theological educators in the coming few years: 1. The pressure to meet student expectations; 2. The pressure to enrich the classroom experience by engaging the visual learner; 3. The pressure to enhance the traditional course through richer pedagogical strategies available with technology; and 4. The pressure to offer distance programs.